Firm Value in the Post-Pandemic Era: The Moderating Role of Board of Commissioners in Indonesian Manufacturing Firms - Permatasari, Rahmadani; Achyani, Fatchan (Journal of Enterprise and Development (JED), 2026)
Purpose: This study examines the effects of corporate social responsibility (CSR), dividend policy, leverage, and profitability on firm value and investigates whether good corporate governance—proxied by the board of commissioners—moderates these relationships.Method: This research employs a quantitative research design using secondary data derived from the annual reports and sustainability reports of manufacturing firms listed on the Indonesia Stock Exchange (IDX) over the 2021–2023 period. Using purposive sampling, 21 firms were selected, yielding 63 firm-year observations. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA).Result: The findings show that leverage and profitability significantly influence firm value, whereas CSR and dividend policy do not have a significant effect. The board of commissioners significantly moderates the relationship between leverage and firm value but does not moderate the relationships of CSR, dividend policy, or profitability with firm value.Practical Implications for Economic Growth and Development: These results highlight the importance of strengthening corporate governance, particularly in capital structure oversight, to support corporate stability and enhance investor confidence—factors that can contribute to sustainable economic growth.Originality/Value: This study advances the corporate finance and governance literature by integrating CSR disclosure, dividend policy, financial performance, and governance structure within a single moderating framework. Using evidence from Indonesia’s post-pandemic manufacturing sector, it provides insight into how governance mechanisms shape the effectiveness of financial decisions in enhancing firm value.